Tau neutrinos in the next decade: from GeV to EeV. (1st November 2022) - Abraham, Roshan Mammen; Alvarez-Muñiz, Jaime; Argüelles, Carlos A; Ariga, Akitaka; Ariga, Tomoko; Aurisano, Adam; Autiero, Dario; Bishai, Mary; Bostan, Nilay; Bustamante, Mauricio; Cummings, Austin; Decoene, Valentin; et al.
Abstract: Tau neutrinos are the least studied particle in the standard model. This whitepaper discusses the current and expected upcoming status of tau neutrino physics with attention to the broad experimental and theoretical landscape spanning long-baseline, beam-dump, collider, and astrophysical experiments. This whitepaper was prepared as a part of the NuTau2021 Workshop.